WORK FROM HOME IMPROVES OR IMPAIRS THE WORK- LIFE BALANCE- A STUDY CONDUCTED AMONG TEACHERS - K.S, Sunitha; Gopal, Nikita (The journal of contemporary issues in business and government, 2021)
In recent years, there has been increasing focus about how to adjust work and life responsibilities in both scholastic and political discussions. Work from home is one activity that has been advanced as a method of improving the work–life balance [1]. Considering this evidence this paper examines the work-life balance experiences of teachers who are working from home during the outbreak of Covid-19. Using the data from 72 teachers selected randomly from different educational institutions of Kerala, it explores the question of whether working (or not) from home improves or impairs teacher‘s capacity to balance their work and life commitments. A Snowball sampling method is adopted for identifying respondents and Chi-square test is used for finding out the variable relationships. The outcomes of the study specify that working from home has a constructive impact on teacher‘s work life Balance. In addition, the result also confirms that working from home certainly increases enthusiasm and satisfaction as teachers are getting more time to spend with their family. It is also found that the use of Information Technology tools in managing the life chores has a significant relationship with Work Life Balance.